Perception of Orthodontists on Posed and Dynamic Smile in Terms of Buccal Corridor Space: A Pilot Study - Kreethika Suresh; Thirunavukkarasu Ramanathan; Sola Rajan (Journal of Clinical and Diagnostic Research)
Introduction: Smile analysis, is an important component of diagnosis and treatment planning. One component of smile analysis is the buccal corridor space. This “negative space” helps orthodontists in planning for a more aesthetic post treatment smile. Studies regarding smile analysis were done with the help of static images. A more comprehensive evaluation can be made with the help of dynamic images. Aim: To access the difference in perception of orthodontists on posed and dynamic smile in terms of buccal corridor space. Materials and Methods: The present pilot study was conducted in the Department of Orthodontics at Karpaga Vinayaga Institute of Dental Sciences, Chengalpattu, Tamil Nadu, India, from September 2024 to December 2024. Fifteen subjects (six males, nine females) aged 18 to 25 years were selected for the study. The subjects were made to sit upright and a video camera at a distance of 10 feet from the subject was stabilised. The subjects were asked to smile and then say the English phrase “Chelsea eats cheesecake on the Chesapeake” and multiple images were captured. The smiles were divided into two groups. Group A: Posed smile and Group B: dynamic smile. The image that was captured before saying the phrase was selected as posed smile and the image that best represented the broadest smile was selected as the dynamic smile. A Google form was created, in which both the posed and dynamic smile pictures were mixed and uploaded. The form was circulated to ten experienced Orthodontists for evaluation. Subjective evaluation was done using Visual Analogue Scale (VAS) to rate the smiles based on buccal corridor space in terms of attractiveness and treatment priority needs. Results: A total of 150 responses were recorded for both posed and dynamic smiles. The scoring given by each Orthodontist for each question was summed up to produce the results. Both posed and dynamic smile were found to have moderate level of attractiveness in terms of buccal corridor space. It also shows that, the broader the buccal corridor space, the need for treatment increases. Conclusion: Even though posed smile is considered to be used as a standard for smile analysis in diagnosis and treatment planning, dynamic smile evaluation can also be taken into account for a better understanding of smile variables.